Clinical features and prognostic analysis of patients with chest wall chondrosarcoma - Gao, Hongliang (Medicine (Baltimore), 2019)
Chest wall chondrosarcoma is a rare malignant tumor of the bone. This study is aimed to identify the prognostic determinants of chest wall chondrosarcoma. We used the Surveillance, Epidemiology, and End Results (SEER) database to identify patients with chest wall chondrosarcoma from 1973 to 2015. Statistical analyses were performed using Kaplan–Meier method and Cox regression proportional hazards. A total of 779 patients were identified from the SEER database. The overall survival (OS) and cancer-specific survival (CSS) rates of the entire group at 10 years were 66.2% and 77.2%, respectively. On multivariate Cox regression, age ≤40 years, localized tumor stage, low tumor grade, surgery, and no radiotherapy were significantly associated with improved both OS and CSS. This study may help clinicians to predict survival of patients with chest wall chondrosarcoma and to provide appropriate treatment recommendations.